13(y+3)=13y+30

Simple and best practice solution for 13(y+3)=13y+30 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 13(y+3)=13y+30 equation:



13(y+3)=13y+30
We move all terms to the left:
13(y+3)-(13y+30)=0
We multiply parentheses
13y-(13y+30)+39=0
We get rid of parentheses
13y-13y-30+39=0
We add all the numbers together, and all the variables
9!=0
There is no solution for this equation

See similar equations:

| 31–3x=1 | | 25/x+22=3/x | | x/32=12/16 | | 2x+4=x-31 | | 9(x+11)=9 | | b-1/4+2b-3/4=b-1/2 | | x^2+5x-2040=0 | | m−1=7 | | ((b-1)/4)+((2b-3)/4)=b-(1/2) | | 2x=(-1/9)x^2 | | ((b-1)/4)+((2b-3)/4)=b-1/2 | | (3x^2)(8x)=0 | | 72=2x-8 | | ((b-1)/4)+(2b-3)/4=b-1/2 | | 7*4^x=89 | | 2(x-3)+5(x-1)=4 | | 5^(3x-1)=24 | | 5^3x-1)=24 | | (10x+30)=(8x-3) | | (4x+16)/(2x+4)=0 | | 2^x=1.03 | | G^2-8g+7=0 | | 7(2-x+9=2 | | (2x+4)/(4x+16)=0 | | (3x+15)+(2x)=90 | | (3x-15)+(2x)=90 | | 42=15+2x | | -7(2t+2)=42 | | -3u+12u+6=7u=30 | | -10(s+3)=-89 | | 12m+50=949.38 | | 2(r+3)-4r=18 |

Equations solver categories